Effects of Sale Promotions on the Purchase Intentions Held Towards Beauty and Cosmetic Products Available Via Cross-Border E-Commerce - Pannapayuk, Suthasinee (2020)
The purpose of this research is to study the effects of sale promotions in cross-border e-commerce (CBEC) on the purchase intentions held towards beauty and cosmetic products. Sale promotions analysis considers different sale promotion type – including flash sales, free shipping, online coupons/coupon codes, campaigns and other supporting factors which influence sale promotions (i.e., frequency and time pressure) on perceived emotional value and purchase intention – through the S-O-R Model. Convenience sampling techniques have been used to produce the sample of this research. A survey was used to collect data relating to the online shopping behaviour of 402 Thai respondents. The SPSS was adopted to analyse the data.